General view of Teplitz on the way toward Schlakenburg - Poppet, John (engraver):::Creator::::::::::::; Wurbs, Karl, 1807-1876 (artist):::Contributor:::::::::::: (Darmstadt; G. G. Lange, 2020)
Engraving with a panoramic view of Teplitz in Bohemia. With an article about Teplitz (4 p.) from an unidentified publication, in German.